The effect of caregiving on bereavement outcome: Study protocol for a longitudinal, prospective study - Breen, Lauren; Aoun, Samar; O'Connor, Moira (BioMed Central Ltd., 2015)
Background: The aim of the current study is to determine the effects of caregiving on bereavement outcome. The study will address two important gaps in the research literature: (1) the relationship between pre-death distress and post-death outcomes and (2) family caregivers' anticipation and preparation of the death of the person for whom they care. Methods/Design: We will conduct a longitudinal, prospective study of adult family caregivers of adult patients receiving palliative care. All participants will complete a questionnaire administered at four points - approximately 4-8 weeks prior to bereavement, and 3-4, 6-7, and 9-10 months post-bereavement. The questionnaire includes measures of multidimensional caregiving experiences (strain, distress, positive appraisals, and family wellbeing), caregiver prolonged grief, multidimensional grief responses (despair, panic behaviour, blame and anger, detachment, disorganisation, and personal growth), prolonged grief, quality of life, general health (psychological and physical) and demographics. These caregivers' data will be compared to a comparison group matched for age, sex, and postcode, allowing the caregivers' general health and quality of life to be compared to a normative group. The caregivers will also be invited to participate in a semi-structured interview about preparing for impending bereavement. Discussion: This is the first study to address the methodological limitations in the current literature and will likely make a significant contribution to both our understanding of caregiving on bereavement outcome and to bereavement care offered in palliative and hospice settings. © 2015 Breen et al.; licensee BioMed Central.